Emergencias y séptimo arte: respuestas constitucionales - Martinez, Leandro Abel (2022)
The manuscript addresses the tools provided by the constitutional system to face emergency scenarios. Furthermore, it aims to help students and the public to understand the anticrisis constitutional framework. Bearing in mind this objective, cinema becomes a valuable educational resource in the teaching and learning process of Constitutional Law. Along the way, it is essential to examine the government?s police power in a state of emergency when imposing restrictions on individual liberties. The COVID-19 pandemic triggers this manuscript. The method proposed for reflection: a variety of films given to us by the seventh art. The final consideration: the restrictions imposed on freedoms based on sanitary emergencies show the tensions between governmental measures and constitutional requirements